Preventive Maintenance Planning 500 Hm on Dump Truck Mercedes Benz Axor 4843k at PT. Mega Jasa Karya Bersama Site PT. Baramulti Sukses Sarana - Imam Hanafi; Anis Siti Nurrohkayati (Procedia of Engineering and Life Science, 2022)
The problem that is often encountered is the service time that has passed from the time specified by the company, namely 500 HM. With the background of these problems, thoughts arise why there can be delays in service time at PT. Mega jasa Karya Bersama. The research method used is preventive maintenance which in this method prevents damage to the unit in operation by scheduling routine maintenance. In this method, replace components so that the unit's life can be longer, and minimize damage. Where in this study also looks for the average hour meter unit for one year, and also the cost of maintenance. The average result of Hm service for 1 year at PT. Mega Jasa Karya Bersama Site PT. Baramulti Suksessarana is 542 Hm. The total maintenance cost of 500 Hm on Dt MJKB-679 for 1 year in 2021 at PT. Mega Jasa Karya Bersama site PT. Baramulti Suksessarana is Rp. 27.440.000 (twenty seven million four hundred forty thousand rupiah). Estimated waktu service time 500 Hm is 25 days.